Augmented reality for construction engineering field (ARG) - Mohd Amizar, Abdul Majid (2015)
This application was developed by using augmented reality technique and focuses on construction engineering field. The project is about how to help architects in perform their blue print design or 2D plan in another more practical way that will show 3D model which look like real scene object without building a prototype as traditional method to perform it. In other words, it will help to impress the client when see the 3D view of the building and also to help engineers to have more understanding of how the building looks like in the real world. Moreover, it will show the traditional model of 2D plan in virtual reality to view in 3D which make the building interior more clearly and can be understood by all users. This augmented reality application is intended to make a new software that uses virtual reality concept to show a new way in presenting the architecture of the construction.